2018
DOI: 10.18203/2320-6012.ijrms20182292
|View full text |Cite
|
Sign up to set email alerts
|

A study of Acinetobacter infections in a tertiary care hospital in Northeast India

Abstract: Background: Acinetobacter is an important opportunistic pathogen and is a common cause of hospital acquired infections. Acinetobacter infections are often extremely difficult to treat because of their widespread resistance to the major groups of antibiotics. The study was conducted to determine prevalence and antibiotic susceptibility pattern of Acinetobacter species isolated from various clinical samples.Methods: Clinical specimens over a period of 2yrs from May 2015 to April 2017 were collected from the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Resistance towards carbapenems like imipenem, meropenem was recorded to be 48(39.3%) and 42(34.4%), respectively. A lower resistance to imipenem (25.3%) and meropenem (29.7%) was reported by Saha et al [11].…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…Resistance towards carbapenems like imipenem, meropenem was recorded to be 48(39.3%) and 42(34.4%), respectively. A lower resistance to imipenem (25.3%) and meropenem (29.7%) was reported by Saha et al [11].…”
Section: Resultsmentioning
confidence: 61%
“…Ampicillin showed maximum resistance and for piperacillintazobactam 56(45.9%). Slightly higher value of resistance for piperacillin-tazobactam 50.5% has been reported by Saha et al [11] Aminoglycosides resistance was observed with 64(52.5%) isolates resistant to gentamicin while Acinetobacter showed more sensitivity to amikacin 107(87.8%). Most studies [7,11] have shown similar high sensitivity(75%-85%) to amikacin and therefore it is considered as one of the drugs of choice in combination with others for treating Acinetobacterspp [27].…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…However, our results are consistent with a recently published study [32] in which antibiotic resistance was greater among biofilm producer K. pneumoniae than non-biofilm producers. Moreover, Saha et al [44] demonstrated that all the biofilmproducing isolates presented more resistance patterns in comparison to non-biofilm producers.…”
Section: Discussionmentioning
confidence: 99%